Dimensional Analysis for Unit Conversions Using MATLAB - Pryor, Roger W. (Mercury Learning and Information, 2018)
This book and MATLAB app package will accurately convert values from one unit of measure to another using standard conversion factors. It performs conversions from and to the inch-pound system units used in the USA and the International System of Units (SI). There are 1,316 conversion factors available for bidirectional conversion from / to SI units, organized into 44 minor subsections by topic under eight major topical sections. There is also an alphabetical section comprising 445 conversion factors for unidirectional conversion to SI units. It also converts CGS and other "unacceptable" units (conversion factors not for general use, i.e. as in science, engineering, etc.). The application performs all three steps in the conversion process: application of the relevant conversion factor, selection of significant digits, and rounding of the result. The unit converter will run on any MacOS or Windows platform that has MATLAB R2018A or R2018B installed